Ride [videorecording (DVD)] - Allyn, Jake; Allyn, Jake; Plasse, Josh; Howell, C. Thomas, 1966-; Gish, Annabeth, 1971-; Smith, Forrie J.; Booth, Laci Kaye; Plasse, Josh (Well Go USA Entertainment, 2024)
Desperate to raise money for his daughter's cancer treatment, a retired bull rider teams up with his estranged son and resorts to robbery to secure payment before time runs out. But after the heist goes awry, keeping the money and their freedom requires the duo to outwit a dogged pair of local law enforcement officers, including a justice-minded sheriff who soon suspects that the key to her case may lie uncomfortably close to home.